قاعدة (العادة م ح ك مة) وأثرھا في الفقھ الإسلامي - أبیش, ا ربح (University of Eloued-جامعة الوادي, 2017)
هذا البحث تحت عنوان (قاعدة العادة محكّمة و أثرها في الفقه الإسلامي) ، وقد يظهر إشكالين رئيسيين : ما مفهوم قاعدة العادة محكمة مع ما يدور حولها من متعلقات؟ و ما هو أثرها في الشرع؟وخلال هذا البحث حاولت الإجابة على هذه الإشكالات وفق الطريقة الآتية: مبحث أول خصصته للحديث حول القاعدة و مفهومها من تعاريف وحجيتها في الشرع و بيان أهميتها ، أما المبحث الثاني خصصته بالحديث عن العادة و العرف من تعريف للعرف و ا، ومجال إعمالها،و ختمته بمبحث ثالث ضمَّنت فيه نمادج 􀂆 ا􀂇 بيان الفروق بين العادة ومتشا توضحية لأثر العادة في الفقه الإسلامي.و توصلت في النهاية لجملة نتائج أهمها :كون العادة محكمة شرعا ، ولها أثر بليغ في الفقه الإسلامي. Summary of the study This research under the title (Custom is the basis of Judgement rule and its impact on Islamic jurisprudence), may appear two Major questions: what a concept usually base a effectiveness with what goes around from attached to it? And what is its impact in religious law?.And during this research I tried to answer these questions in the following way: Discussing the first organize to talk about the rule and its concept of definitions and authority in Islam and a statement of importance, either the second organize devoted to talking about the usual and Custom definition of custom and statement of differences between usual and its similars, and the area of its work, and the third subject which included sealed models explain the impact in Islamic jurisprudence.And eventually reached inter results: that habit, effectiveness and its impact in Islamic jurisprudence.
مذكرة ليسانس
Keywords: قاعدة العادة محكمة /الفقه الاسلامي; La règle de la coutume est courtoise / Jurisprudence islamique